Treatment of Synthetic Wastewater Using Horizontal Subsurface Flow Constructed Wetland - Sarafraz, Sanaz (2008)

(untitled)
Constructed wetland is an effective wastewater treatment technology which is used in worldwide. Nevertheless, the effectiveness of using this wastewater treatment is depending on the selection of the type of design used and other factors. This research was conduced to test the influence of media and vegetation subsurface flow constructed wetlands, designed based on the first-order plug flow kinetics. In this study, four horizontal subsurface flow wetlands (HSSF), each with dimensions of 1.3 m (L) × 0.5 m (W) ×0.4 m (D), were constructed at the Research Station of Tehran University, located in Karaj, Iran. The study was carried out from April to September, 2007. Gravel and zeoilte were used in this study as substrate. Gravelbeds with and without plants, and gravel-beds mixed with 10% zeolite, with and without plants were examined to investigate the feasibility of treating synthetic wastewater which was specially produced and modified to imitate agricultural wastewater. The average synthetic influent wastewater contained approximately 100 mg l-1 Nitrate (NO3-N), 10 mg l-1 total Phosphorous, 10 mg l-1 Zn (II), 2 mg l-1 Pb (II) and 1 mg l-1 Cd (II), while the macrophytes selected were Phragmites Australis and Juncus Inflexus in combine with each other. Water discharge was 65 l / day for each cell, and retention time (HRT) was 1.4 d. The influent and effluent Zn, Pb, Cd, P and NO3-N concentrations were monitored and analyzed every 15 days to assess the performance of the wetland units for removal efficiencies based on the statistical analyses. Two intermediate samples were also collected from each cell to evaluate the values of pollutant concentrations, the parameters along the units, and the effect of the HRT. At the end of the study, plants were harvested and analyzed for the same factors (NO3, P, Zn, Pb and Cd). The results derived indicated that the system had acceptable and optimal pollutant removal efficiency, and that both plants were found tolerant under the tested conditions. The wetland system could achieve the NO3-N removal of 79.19% in vegetated cell with gravel and 10% zeolite as substrate, and 86.58% in an unvegetated cell with gravel and 10% zeolite as substrate, and 82.39% in vegetated cell with gravel as substrate, and finally 87.94% in unvegetated cell with gravel as substrate. As for the P removal, the efficiencies of 93.12%, 89.47%, 81.76% and 76.65% were respectively achieved for the vegetated cell with gravel and zeolite as substrate, the vegetated cell with gravel as substrate, unvegetated cell with gravel and zeolite as substrate, and unvegetated cell with gravel as substrate. The outflow concentrations of Pb and Cd were found to be under the detection limit; however, as for Zn, the removal efficiencies of 99.9%, 99.76%, 99.71% and 99.52% were concluded for the vegetated cell with gravel and zeolite, unvegetated cell with gravel and zeolite, vegetated cell with gravel, and unvegetated cell with gravel, respectively.